Tantangan dan Peluang Otoritas Jasa Keuangan dalam Era Digitalisasi Layanan Keuangan - Riska Riska; Seri Mughni Sulubara (JURNAL RISET MANAJEMEN (JURMA), 2024)
The Financial Services Authority (OJK), which has a position as a state institution, was formed based on Law Number 21 of 2011. OJK functions to organize an integrated system of regulation and supervision of all activities in the financial services sector, both in the banking sector, capital markets, and non-bank financial services sectors such as insurance, pension funds, financing institutions, and other financial services institutions (Sulubara, 2023). The Constitutional System of Indonesia (UUD 1945) emphasizes that the Indonesian government system is based on law. In facing challenges and opportunities must be resolved legally. The theoretical studies related to this research are using the theory of legal protection (Musyafah, 2019). This research uses a normative juridical method with the aim of analyzing the role of functions attached to the Financial Services Authority (OJK) in accordance with the legislation as the basis for its formation. The challenges faced by the Financial Services Authority in the era of digitalization of financial services are data security and cyber threats, adaptive regulations, digital divide, digital literacy and dependence on third parties. Meanwhile, the opportunities presented by the digitalization of financial services are financial inclusion, product and service innovation, ecosystem collaboration and digital asset development.